ATTITUDINAL FACTORS OF FISHERMEN TRAPPED IN THE B40 CATEGORY: AN EMPIRICAL STUDY (Journal of Technology and Operations Management, 2024)
The fishing industry plays an important role in global economic development. However, its importance is not in line with the well-being of key players in the fishing industry itself, especially Zone A fishermen who are mostly in the Bottom 40% (B40) of household income category. Although the government has emphasised this issue by providing various programmes and funds that are suitable for fishing activities by Zone A fishermen, there are still some Zone A fishermen who are at the poverty level. Thus, the objective of this article investigated the causes of low well-being among B40 fishermen from the aspect of the individual. The result of the study combined two data sources, namely primary data and secondary data. A qualitative approach was conducted by interviewing 23 informants consisting of Zone A fishermen and directors involved in fishing activities. This study was conducted in three states, namelyPerlis, Terengganu, and Melaka. The results of the interviews were transcribed in the form of verbatim data, that is, word extracts from informants. Verbatim data were analysed using thematic analysis involving the process of coding, categorization, and finally theme production to answer the research questions. The findings of the study found that individual factors do affect the well-being of B40fishermen. Individual factors can be classified into two, namely internal and external factors. Individual factors are internally divided into attitudes, interests, knowledge of fishermen, experience, skills, selfmotivation, and also creativity. Meanwhile, external factors are divided into alternative income, family support, and also hereditary fishermen. Hopefully, the important findings in this study can assist to improve the economic standing of the fishing community. At the same time, support and encouragement from families, communities, and the government is important to change the attitude of fishermen to get a better life and get out of poverty in the B40 community. Furthermore, to get an overview of the wellbeing of fishermen in Malaysia, it is proposed that future studies can increase the number of states and informants, and use a mix method approach or quantitative methods to further provide more finding for the betterment of the fishing communities.